Screening of Blood Glucose Concentration in Domestic Cat (Felis Catus) Based on Body Condition Score, Breed, and Sex Using Portable Blood Glucose Meter - Billa, Lutfiah Annisa; Triakoso, Nusdianto; Rachmawati, Kadek; Yuniarti, Wiwik Misaco; Aksono, Eduardus Bimo; Yudaniayanti, Ira Sari (Journal of Basic Medical Veterinary, 2023)
Type 2 diabetes mellitus (T2DM) is a common endocrine disease in domestic cats. Breed, sex, being overweight to an extent of obesity are predisposing factors for developing T2DM. One of the most common laboratory analyses conducted to confirm this disease is blood glucose concentrations. The aim of this research is to determine blood glucose concentration in domestic cats based on BCS, breed, and sex using a portable blood glucose meter. Research samples were obtained by taking blood samples from the marginal ear vein of 131 domestic cats that matched the sample's criteria, took at 2-hours post prandial, and drip onto the Sinocare strip. The results showed that the average blood glucose concentration was in the normal range, with a total of ideal (BCS ≥3/5) domestic cats (n=43) was 75.74 mg/dL, overweight (BCS ≥4/5) domestic cats (n=44) was 78.23 mg/dL, obese (BCS ≥5/5) domestic cats (n=44) was 89.66 mg/dL, male (n=51) was 80.57 mg/dL, female (n=80) was 81.69 mg/dL, Mixed Breed (n= 119) was 81.03 mg/dL, Angora (n=5) was 84.20 mg/dL, Persian (n=6) was 81.50 mg/dL and Ragdoll (n=1) was 92 mg/dL. Pearson correlation showed BCS (r=0.403; p= 0.000) had a moderate, positive, and significant correlation with blood glucose concentration in domestic cats. Meanwhile, the results of Kendall's Tau correlation showed that breed (p=0.740) and sex (p=0.555) had insignificant correlation with blood glucose concentration in domestic cats.